Mekanisme Promosi dan Demosi dalam Pengembangan Karir Guru di SMA Labschool UNESA 1 - Sabrina Putri Fanisa; Siti Uswatun Khasanah; Shilfiana Amelia Putri; Syunu Trihantoyo; Nuphanudin Nuphanudin (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research aims to determine the impact of promotion and demotion mechanisms in teacher career development at SMA Labschool Unesa 1. This research uses a qualitative approach. The type of research used is interviews. The informant in this research was only one teacher. This research shows the mechanism of promotion and demotion in teacher career development at SMA Labschool Unesa 1. There are promotion and demotion indicators consisting of work performance, discipline, skills. Lastly, the demotion indicators consist of member incompetence, personal requests, and rationalization of numbers. The results of the discussion in this research are that in carrying out professional duties, teachers have the right to receive promotions in accordance with their duties and work performance, which includes promotion/increase in functional position. Furthermore, demotions are caused by the lack of performance of a teacher who is not good enough. Demoting a teacher does not happen directly, but there is a gradual evaluation, namely by evaluating several times with agreement with the other teachers. At SMA Labschool Unesa 1, there are no differences and there is a sense of family towards teachers who have just been demoted.